How to keep one's place AD 1833. - Heath, William, 1795-1840 - also known as Paul Pry ? (McLean, Thomas, 1829)
Scholarly notes may be added at a later date.
1 print : col.
Keywords: Caricatures; Cartoons; Ireland -- Politics and government -- 1800-1837